IMPLEMENTATION FINANCING AT THE MUKTAR SYAFAAT MIDDLE SCHOOL - Hafid, Ahmad Nur; Ekaningsih, Lely Ana Ferawati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Effective and efficient financial management is an important element in supporting the continuity and quality of education, especially in Islamic boarding school-based schools such as MTs Muktar Syafaat . This research aims to analyze the priority-based financing planning approach applied at MTs Muktar Syafaat in managing two main sources of funding: sharia payments and school operational assistance (BOS). This research uses descriptive qualitative methods with data collection techniques through in-depth interviews, observation and document study. The research focus includes identifying primary and secondary needs as well as funding allocation mechanisms based on priorities. The research results Operational funding at MTs Muktar Syafaat relies on two main sources: sharia payments and School Operational Assistance (BOS). Sharia payments, in the form of mandatory student contributions, are the main foundation of madrasah financing, used for teacher salaries, teaching materials, and facility maintenance. These funds are also managed by foundations to support other units, such as Islamic boarding schools and mosques. However, this system is vulnerable to fluctuations in revenue, especially during economic instability, such as crises or pandemics. Dependence on the economic capacity of the guardians of students poses a challenge, although the foundation provides payment flexibility.